La censura de la poesía en el humanismo cristiano: La Apología del cisterciense Lorenzo de Zamora - Nieto Ibáñez, Jesús María (2017)
In 16th- and 17th-century Humanist literature the Apología contra los que reprehenden el uso de las humanas letras en los sermones y comentarios de la Santa Escritura by the Spanish Cistercian Lorenzo de Zamora (1554–1614) defends the use of Greek and Latin texts in explaining the Holy Scriptures. But it still retains the typical criticism of certain products of Classical authors, such as poetry or theatre, along the well-known lines of the apologetics of the early centuries of Christianity.
Keywords: Zamora, Lorenzo de, -- m. 1614; Poesía; Humanismo cristiano; Censura